A Resource Allocation Algorithm Based on Subcarrier Pairing in Multi-User Cooperative Relay Communication - Bin Chen; Youming Li; Tao Guo; Peng Lei; Xiaoqing Liu (Dianxin kexue)
For the power minimization problem in multi-user cooperative relay communications,a resource allocation algorithm based on joint subcarrier pairing and assignment was proposed.Firstly,according to the average channel gain and the target rates of user,the assignment of subcarrier numbers was addressed.Then,in order to choose the subcarrier with best channel condition,a multi-user iterative algorithm for joint subcarrier pairing and assignment was proposed,which could achieve the subcarrier pairing in the cooperative transmissions and virtual pairing in the direct transmission,respectively.Finally,the power allocation was conducted by the water-filling algorithm,so that each user could use the minimum power for transmission.The simulation results indicate that the proposed algorithm can conduct subcarrier pairing and assignment effectively to minimize the total transmission power while meeting the users' target rate requirement.